In vitro and in vivo cardioprotective and metabolic efficacy of vitamin E TPGS/Apelin. (January 2020) - Leme Goto, Patricia; Cinato, Mathieu; Merachli, Fadi; Vons, Bohdana; Jimenez, Tony; Marsal, Dimitri; Todua, Nika; Loi, Halyna; Santin, Yohan; Cassel, Stéphanie; Blanzat, Muriel; Tronchere, Helene; et al.
Abstract: Aims: Apelin and vitamin E have been proposed as signaling molecules, but their synergistic role is unknown. The aim of this work was to develop vitamin E TPGS/Apelin system to test their cardioprotective and metabolic efficacy in vitro and in vivo. Methods: FDA-approved surfactant D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS-1000) and Apelin complex were characterized by physico-chemical methods (CMC determination, dynamic light scattering and circular dichroism). In vitro studies were carried out on H9C2 cardiomyoblasts and isolated murine cardiomyocytes. In vivo studies were performed in isoproterenol- and high-fat diet-induced cardiac remodeling models in mice. Results: We found that vitamin E TPGS/Apelin provide cardioprotective and metabolic efficacy in vitro and in vivo. In vitro studies revealed that vitamin E TPGS/Apelin reduces hypoxia-induced mitochondrial ROS production in cultured cardiomyocytes and H9C2 cardiomyoblasts. In addition, vitamin E TPGS/Apelin confers apoptotic response to hypoxic stress in cells. In a mouse model of isoproterenol - induced cardiac injury, TPGS is not able to affect cardiac remodeling, however combination of vitamin E TPGS and Apelin counteracts myocardial apoptosis, oxidative stress, hypertrophy and fibrosis. Furthermore, combination treatment attenuated obesity-induced cardiometabolic and fibrotic remodeling in mice. Conclusion: Together, our data demonstrated the therapeutic benefits of vitamin E TPGS/Apelin complex to combat cardiovascular and metabolic disorders. Highlights: Combination of TPGS-1000 and Apelin-13 prevents oxidative stress and apoptosis in response to hypoxia in cardiac cells. Apelin-13 but not TPGS-1000 treatment dampens isoproterenol-induced myocardial injury in mice. Combination treatment reduces cardiac apoptosis, oxidative stress and metabolic disorders in obese mice. TPGS-1000/Apelin treatment improves cardiac function in obesity-associated heart failure.